Nicotinamide Riboside, an NAD + Precursor, Reduces Hepatic Stellate Cell Activation and Attenuates Liver Fibrosis in a Diet-induced Mouse Model of Liver Fibrosis (OR24-06-19). (13th June 2019) - Pham, Tho; Bae, Minkyung; Kim, Mi-Bo; Lee, Yoojin; Hu, Siqi; Kang, Hyunju; Park, Young-Ki; Lee, Ji-Young
Abstract: Objectives: There is limited pharmacological treatment for liver fibrosis, which can result from chronic liver injury. In this study, we investigated the effect of nicotinamide riboside (NR), a nicotinamide adenine dinucleotide (NAD) precursor, on the development of liver fibrosis in a diet-induced mouse model of liver fibrosis in vivo and in hepatic stellate cells (HSCs) in vitro. Methods: Male C57BL/6 J mice were randomly assigned to three groups: a low-fat control (LF; 6% fat by wt), a high-fat/high-sucrose/high-cholesterol control (HF; 35%/34%/2.0% by wt, n = 13) or a HF diet supplemented with NR at 400 mg/kg/day (HF-NR, n = 14) for 20 weeks. Features of liver fibrosis were assessed by molecular, histological, and biochemical analyses to determine the effect of NR. Metabolic rates, energy expenditure and physical activity were measured using indirect calorimetry. Primary mouse and human HSCs, the primary extracellular matrix-producing cell-type in the liver, were used to determine the anti-fibrogenic effects of NR in vitro. Results: HF-NR group had reduced body weight gain, which was attributable to increased energy expenditure. NR supplementation did not affect serum alanine aminotransferase levels and markers of steatosis and inflammation in the liver. However, liver trichrome and picrosirius red staining and total collagen quantification showed significant reductions of collagen by NR. Consistently, hepatic collagen 1a1 mRNA and protein were significantly reduced in the HF-NR group. Liver NAD levels were significantly reduced by HF, but was increased by NR supplementation. RNA-Seq analysis of NAD metabolism genes in quiescent and activated HSCs indicated that NAD levels might be reduced in activated HSCs due to repression of NAD salvage pathway, which regenerates NAD from nicotinamide. Indeed, treatment of primary human and mouse HSCs with NR significantly reduced their activation in vitro. Conclusions: NR supplementation prevented the development of liver fibrosis in a diet-induced mouse model of liver fibrosis independent of hepatic steatosis and inflammation. The data suggest that NR may directly reduce HSC activation to exert its anti-fibrotic effect. NR may be developed as a potential preventative for human liver fibrosis. Funding Sources: The NIH, USDA Multistate Hatch, and USDA Hatch.